Romanticism In Lord Byron Selected Poems Entitled It Is The Hour. So We Will Go No More Roving, She Walks In Beauty, The First Kiss Of Love And Remind Me Not, Remind Me Not - Lubis, Zulfikar; Moelier, Dahlia D.; Asyrafunnisa, Asyrafunnisa (Humaniora: Journal of Linguistics, Literature, and Education, 2024)
Abstract This study aims to find the characteristic of how the romanticism and portrayed as reflected in Lord Byron selected poem entitled It is the Hour, So We Will Go No More Roving, She Walks in Beauty, The First Kiss of Love and Remind me not, Remind me not. This research is expected to be a reference for future researchers. The data source used in this research is a poem. In analyzing the data, the writer used a qualitative descriptive research method. The data were obtained by using reading, note-taking, and analyzing techniques through a romanticism approach to literary works and to classify the characteristic of romanticism that contained in the 5 poems by Lord Byron using the theory of William Wordsworth. There are 7 characteristics of romanticism in the theory and the researcher found there are 6 characteristic of romanticism that reveals on the 5 poems by Byron, 26 data of romanticism characteristic and 5 data of romanticism portrayed. Most of the poem line by Byron, intensively used romanticism characteristic to express emotional feeling, nature, spontaneous, human relationship and best experience about human being